A man called Peter - Marshall, Catherine, 1914-1983.; Ertl, Renee (Carol Stream, IL : Oasis Audio, 2010)
The biography of the Presbyterian minister who became chaplain of the U.S. Senate.
Unabridged.
Compact disc.
In container (14 x 17 cm.).
Read by Renee Ertl ; foreword written and read by Peter F. Marhsall.
Keywords: Marshall, Peter, -- 1902-1949.; United States. -- Congress -- Chaplains -- Biography; Presbyterian Church -- United States -- Clergy -- Biography; Immigrants -- Biography; Scottish Americans -- Biography